Frequency of Isolation of Methicillin-resistant Staphylococcus Aureus (MRSA) from Pus Samples and its Antibiotic Susceptibility - Rubab, Fatima; Majid, Muhammad; Zeb, Anam; Shabbir, Sundas; Ali, Nayab; Ali, Sakhawat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the frequency of isolation of methicillin-resistant Staphylococcus aureus from pus samples and the invitro efficacy of commonly used antimicrobial drugs against them. Study Design: Cross-sectional study Place and Duration of Study: Department of Microbiology, Army Medical College, National University of Medical Sciences,Rawalpindi, from May 2018 to Apr 2019. Methodology: The pus samples were subjected to standard microbiological procedures. The Kirby Bauer disc diffusion method was used to determine the antibiotics susceptibility pattern of the isolates, and results were interpreted according to Clinical and Laboratory Standards Institute (CLSI) guidelines-2018. Results: Of the total 499 Staphylococcus aureus, 214(42%) were Methicillin-Resistant Staphylococcus aureus. The resistance against antibiotics were found in penicillin 214(100%), Trimethoprim/Sulfamethoxazole 205(96%), Erythromycin 177(82.7%),Ciprofloxacin 160(75.3%), Chloramphenicol 131(61%), Gentamicin 88(40.9%), Tetracycline 52(24%), Fusidic Acid 35(16%),Clindamycin 33(15.3%), Minocycline 11(5.2%), Vancomycin and Linezolid (0%). Conclusion: There is a high frequency of MRSA in our setup with very limited treatment options.